Guide to Performing McMaster’s Fecal Egg Count for Small Ruminants - Bridget Stice; Laura H. Bennett; Christa L. Kirby; Allison L. Williams; Brittany N. Diehl (EDIS)
This article is meant to serve as a general guide to perform quantitative fecal egg counts on grazing small ruminants, specifically sheep and goats. This tool is utilized to estimate the extent of pasture parasite burden as well as individual animal parasite burden, and to determine the efficacy of dewormer or anthelmintic treatment. Written by Bridget Stice, Laura H. Bennett, Christa L. Kirby, Allison L. Williams, and Brittany N. Diehl, and published by the UF College of Veterinary Medicine, UF/IFAS Extension, December 2024.